Uma arquitetura para incorporação modular de aspectos de segurança em aplicações peer-to-peer. - Detsch, André (Universidade do Vale do Rio do Sinos, 2005)
Peer-to-peer (P2P) applications are becoming increasingly important in academic environments and, in particular, corporative ones. In such environments, the wide adop- tion of P2P applications is subject to the fulfilment of several security requirements, including authentication, confidentiality, and authorization. There exist approaches that aim to provide specific security needs, but have two disadvantages: cannot be employed integratedly, and require the user/application programmer to manipulate a complex pro- gramming interface, followed by a cumbersome configuring process. This thesis presents a security architecture that isolates from the P2P application and the underlying com- munication middleware the implementation and configuration of security aspects. The latter are achieved through independent modules that implement well-known security techniques. The architecture was implemented using JXTA, a popular P2P middleware. As a study case, the architecture was incorporated to OurGrid, an applicati
An architecture for the modular inclusion of security aspects in peer-to-peer applications
Keywords: arquitetura de segurança; peer-to-peer; arquitecture of security; peer-to-peer; Ciências Exatas e da Terra